KONTRIBUSI PERPUSTAKAAN DESA LENTERA DALAM PEMBERDAYAAN EKONOMI KREATIF MASYARAKAT DESA TEPI LAUT BENGKULU UTARA - Darti, Darti Daryanti (UPT Perpustakaan Universitas Bengkulu, 2023)
This research aims to find out how the Lentera village library contributes to empowering the creative economy of the North Bengkulu Seaside Village community. This research uses a qualitative research method with a case study approach. The research subject is the Lantera Library of Tepi Laut Village, Air Napal District, North Bengkulu Regency, which facilitates the community, especially PKK women, to make creative economy handicrafts. Meanwhile, the object of this research is the thing that will be studied, namely the contribution of the Lantera Village library in empowering the creative economy of the people of North Bengkulu Seaside Village. Based on the research results, it was found that the Lentera Village Library has a role in the creative economy, namely by providing training regarding skilled and creative (Tertif), such as skilled and creative Handycraft and skilled and creative culinary. These skills can be in the form of: (1) Crafts of Making Flowers from Used Items; (2) Bead-rolling skills; (3) Gold thread embroidery skills; (4) Skills in making piggy banks from used cans; (5) Skills in making typical Bengkulu by tat cakes. The Tepi Laut Village Library also helps in empowering the people in the Tepi Laut Village who initially did not understand how to make crafts until the products could finally be sold, as well as people who did not understand how to market products, to understand how to market products to a wide market reach.